Metabolic dysfunction associated steatotic liver disease in Patients with Hypothyroidism: a single centre study - Bisht, A; Bajracharya, MR; Mall , D; Karki, BB; Shrestha, PS; Adhikari, BB; Prajapati, S; Karki, ST; Nepal, R; Wasti, KP; Shah, TP; Sinjali , NK (Journal of Diabetes and Endocrinology Association of Nepal, 2025)
Background: Hypothyroidism is a potential modifiable factor for metabolic dysfunction associated steatotic liver disease (MASLD). MASLD is associated with diminished thyroid action. Hypothyroidism causes reduction in uptake of free fatty acid and decreased lipolysis in the adipose tissue resulting in hepatic accumulation of triglycerides and increased low-density lipoprotein uptake. Hypothyroidism also increases triglyceride which contributes to hepatic insulin resistance, a factor for MASLD. Methods: A hospital based cross-sectional study was conducted at National Academy of Medical Sciences, Bir hospital on 28 newly diagnosed overt or subclinical hypothyroidism patients as hypothyroid group and matched 28 euthyroid patients visiting wellness clinic as comparison group who qualified for the eligibility criteria. The prevalence of MASLD in both groups was determined by ultrasonography (USG) which was done by a single radiologist. Results: The mean ages in hypothyroid and euthyroid groups were 41.07 years and 39.71 years respectively. The female to male ratio in hypothyroid was 3.6:1 and 1.5:1 in euthyroid group. MASLD was present in 15 (53.6%) hypothyroid and 7 (25%) of euthyroid group which was statistically significant (p value 0.029). Severity of MASLD was seen more in hypothyroid patients. There was no statistically significant correlation between thyroxine (T4), thyroid stimulating hormone (TSH) and severity of MASLD. Conclusion: Hypothyroidism is associated with MASLD and severity of MASLD is more with hypothyroid patients as compared to euthyroid group.